If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -6) + 6 = 3(x + -6) Reorder the terms: 5(-6 + x) + 6 = 3(x + -6) (-6 * 5 + x * 5) + 6 = 3(x + -6) (-30 + 5x) + 6 = 3(x + -6) Reorder the terms: -30 + 6 + 5x = 3(x + -6) Combine like terms: -30 + 6 = -24 -24 + 5x = 3(x + -6) Reorder the terms: -24 + 5x = 3(-6 + x) -24 + 5x = (-6 * 3 + x * 3) -24 + 5x = (-18 + 3x) Solving -24 + 5x = -18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -24 + 5x + -3x = -18 + 3x + -3x Combine like terms: 5x + -3x = 2x -24 + 2x = -18 + 3x + -3x Combine like terms: 3x + -3x = 0 -24 + 2x = -18 + 0 -24 + 2x = -18 Add '24' to each side of the equation. -24 + 24 + 2x = -18 + 24 Combine like terms: -24 + 24 = 0 0 + 2x = -18 + 24 2x = -18 + 24 Combine like terms: -18 + 24 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| 1/5.1/5.1/5= | | 8q*7q^4= | | -5(5y-6)+3(2y+6)= | | y+8-2(y-20)=0 | | 0.04=0.5x-2 | | 7m*3= | | 10-(x+5)=6x-2 | | 1.1x+3.3=0.6x+1.75 | | 1.1x+3.3=0.6+1.75 | | 2x+36=10x-4 | | 2n-12=3n+27 | | -3-(6-5p)= | | 9j-3k-4j+5k= | | 3(x-4)-4=5x | | 23=3x+2 | | 3(x-6)+2=4(x+2)+21 | | 5z=10 | | -3-(2-2p)= | | 8(3x+1)=16 | | 28r^4+16r^3-80r^2=0 | | x=3*x-4 | | 6.4x=38.4 | | 7(n+8)+6(1+4n)=-31 | | 12-8x=50-15x | | -68-8x=7x | | 8m-11m=-12 | | 3x+13=-47-9 | | 8r+17=4(6r+6)-7 | | 7(4x-5)= | | 12(2x-1)-5(3y+2)=8 | | 149-5x=40x+13 | | 8-7n+4n=18-76 |